การคัดเลือกพันธุ์เห็ดหมื่นปี Ganoderma lucidum (Fr.) Karst. พันธุ์ลูกผสมที่มีปริมาณพอลิแซกคาไรด์สูง - ยุพาพรรณ ระลึก (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The growth rate of Lingzhi mushroom Ganoderma lucidum (Fr.) Karst 9 strains grown in PDA media, PDB media, millet media and saw-dust media were determined that the highest growth rate was MUG001 followed by MUG100 and MUG101 by sequence.The others are have growth rate and weight rate lower than that. Reproduction by monosporous culture determine that MUG001 reproduct 10 spores.While MUG100 reproduct 8 spores.Crosses 9 strains by Buller phenomenon method found compatible di-mon crosses total 5 hybrid strains.While the others incompatible di-mon.The growth rate of 5 hybrid strain are equal to native strain. The amount of polysaccharides that analyzed by the phenol-sulfuric method determine that MUG001 MUG003-UV-cv1 MUG101 and MUG100 have the most amount of polysaccharides at 1 gram of mycelium dry weight there are 48.94, 33.78, 32.73 and 24.78 mg. at 1 g. of mycelium dry weight sequence. The others have lower than that.While crosses strains H1, H2, H3, H4 and H5 have polysaccharides 29.12, 26.18, 19.78, 30.64 and 25.09 mg. at 1 g. of mycelium dry weight by sequence. The amount of DNA that extracted by perchloric acid and the amount of DNA were measured by Diphenylamin method. When calculated the ratio between the amount of polysaccharides with the amount of DNA determine that MUG001 MUG101 MUG003-UV-cv1 and MUG100 have 9.97, 9.79, 7.17 and the ratio between the amount of polysaccharides with the amount of DNA.The others have lower than that.While hybrid strains H5 have the ratio between the amount of polysaccharides with the amount of DNA more that native strains it has 7.77 while native have 7.17 and 7.74. The others hybrid strains have ratio equal to native strains.